2014
DOI: 10.1093/conphys/cou052
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary reliance on bicarbonate acquisition predicts increased growth of seagrass Amphibolis antarctica in a high-CO2 world

Abstract: We find energetically costly bicarbonate pathways exist in three temperate seagrasses and then provide evidence that indicates greater growth and photosynthetic efficiency for bicarbonate users in a high CO2 world. Greater growth might enhance the future prosperity and rehabilitation of these important habitat forming plants, which have experienced declines of global significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Studies had indicated that greater availability of DIC under future OA conditions may benefit seagrasses [ 13 15 ]. An increase in photosynthesis and growth following exposure to increased DIC in both tropical and temperate species was previously demonstrated [ 16 22 ]. Moreover, since tropical and temperate seagrasses displayed a higher photosynthetic affinity for CO 2 than HCO 3 - , an increased availability of CO 2 can further boost productivity [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Studies had indicated that greater availability of DIC under future OA conditions may benefit seagrasses [ 13 15 ]. An increase in photosynthesis and growth following exposure to increased DIC in both tropical and temperate species was previously demonstrated [ 16 22 ]. Moreover, since tropical and temperate seagrasses displayed a higher photosynthetic affinity for CO 2 than HCO 3 - , an increased availability of CO 2 can further boost productivity [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 90%
“…At natural CO 2 vent sites, growth and areal cover of seagrasses were observed to be much greater than at adjacent non-CO 2 enriched sites [ 15 , 25 ]. Hence, given sufficient light and nutrient availability, seagrasses could utilise the extra provisioning of DIC to enhance productivity [ 9 , 22 , 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower CR during exposed condition may increase the overall community production of exposed Z. noltei compared to submerged conditions where CR rates are higher. As well, during submersion Z. noltei favors the utilization of bicarbonate directly or indirectly to increase its production (Hellblom et al, 2001), but this process is energy intensive (Burnell et al, 2014), whereas the air exposed community during exposure, because of its high affinity and high availability of CO 2 in future conditions, can easily use the CO 2 from the atmosphere for community production (Touchette and Burkholder, 2007). The other factors that can contribute to the higher production of air-exposed Z. noltei community under CO 2 enriched conditions can be high light intensity and low turbidity.…”
Section: Co 2 Enrichmentmentioning
confidence: 99%